The Umbrella Academy. Season one [videorecording (DVD)] - Page, Elliot, 1987-; Hopper, Tom, 1985-; Castañeda, David, 1989-; Raver-Lampman, Emmy; Sheehan, Robert, 1988-; Gallagher, Aidan, 2003-; Blige, Mary J. (Universal Pictures Home Entertainment, 2021)
The live-action series follows the estranged members of a family of superheroes known as the Umbrella Academy. Years after disbanding, the siblings reunite after the death of their adoptive father, who trained them to save the world years ago. Each possessing unique powers and personalities, the dysfunctional members of the Umbrella Academy include Luther, Diego, Allison, Klaus, Number Five, and Vanya.